Dalla “crisi dell’emergenza rifiuti” alla “Terra dei Fuochi”: profili giuridici a margine della recente sentenza della Corte EDU (Società e diritti, 2025)
This contribution aims to examine the social and legal analysis of the waste emergency in Campania, particularly in light of the institutional utopia of a “European Recycling Society” stemming from Directive 2008/98/EC. The study will then focus on the judgment of conviction issued by the European Court of Human Rights in the case of Cannavacciuolo and others v. Italy and the measures that the Italian State will have to adopt over the next two years, in line with the principle of prevention. Furthermore, an analysis of the content of Directive (EU) 2024/1203, issued on April 11, 2024, will explore prospects for reform in the criminal protection of the environment. This directive has introduced new offenses to combat environmental crime from a repressive perspective, including considerations on the possible implementation of the new crime of “ecocide”.